TINGKAT PENDAPATAN UMKM KOTA PALEMBANG (SURVEY UMKM YANG MELAKUKAN PENJUALAN ONLINE MELALUI SHOPEELIVE) - Andani, Herlin; Anggraini, Leriza Desitama; Sari, Rafika (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This research is a quantitative study aimed at assessing the impact of online sales through the Shopeelive platform on the level of Micro, Small, and Medium Enterprises (MSMEs) in the city of Palembang. The data used in this study consisted of primary data obtained through the use of questionnaires and secondary data sourced from the Cooperative and SME Office of Palembang City. The method applied in this research is simple linear regression analysis. The findings of this research indicate that the Shopeelive variable has a positive influence on the income level of MSMEs in Palembang City.